PENGEMBANGAN AGRO-INDUSTRI PERDESAAN DENGAN PENDEKATAN ONE VILLAGE ONE PRODUCT (OVOP) (Forum Penelitian Agro Ekonomi, 2024)
Agro-industry development in rural areas could be implemented using an OVOP approach. As a people movement, this agro-industry needs active participation of all related institutions.  The inter-related elements under the agribusiness system on this approach requests willingness of all related parties, from the upstream to the downstream of agricultural system cycle. The working steps for its application cover the selection of local specific product, identification of product strengths and associated constraints for development for higher quality and for global market, application of product development (processing and marketing) for added value and income improvement, and implementation of evaluation for better future product and business performances.  The OVOP approach could be applied in rural areas of Indonesia if all stakeholders along with their respective institutions are in favor of the rural people’s interest.